STRATEGY DEVELOPMENT OF ELECTRICAL POWER SUPPLY SYSTEM (EPSS) THE GASH BARCA - A M Berhane; V Yu Abramov (RUDN Journal of Engineering Research, 2015)
The main objective of the development strategy of the power supply system of Gash Barka region is solving the optimization problems of the system of electrical power supply of Gash Bara (SEOSGB). This is done by reducing the initial capital and operating costs, improve power quality and reliability for consumers Electrical Supply. In this paper, we develop the following three options of electrical power systems: electric power system Gash Barka excluding autonomous diesel generators that exist in the province (that new electrical power supply system will be powered by a central power supply system of Eritrea and the existing diesel generators can be used as a backup during a power outage or emergency); the electrical power supply system which powers only twelve of the fourteen areas under the Gash Barka region from the central system power supply of Eritrea (the other two areas under the Gash Barka region will be powered by autonomous diesel generators; the system can automatically switch on to a backup power source in the event of an accident, or when there will be a power outage on either side of the power system); the electrical power supply system which powers only eleven of the fourteen areas under the Gash Barka region from the central power supply system of Eritrea (and the other two sub zones of Gash Barka will be powered by autonomous diesel generators; the system can automatically switch on to a backup power source in the event of an accident or, when, ever there will a power outage on either side of the power system)